Analisis Pola Asuh Orang Tua dalam Membentuk Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen Kelas X di SMAN 1 Kasongan - Jesica Carolina; Riky Riky (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This research is motivated by the importance of the role of learning motivation as the main determinant of students' academic success, which is not only influenced by the school environment but also significantly determined by parental upbringing at home. At SMA Negeri 1 Kasongan, a phenomenon of diverse levels of learning motivation among tenth-grade students was found, where some students are active and diligent, while others are less disciplined, rarely attend, and even prefer to work. The main objective of this research is to conduct an in-depth analysis of the application of parenting styles and their contribution to shaping the learning motivation of tenth-grade students in the subject of Christian Religious Education. The research approach used is descriptive qualitative with purposive sampling technique. “Primary data were collected thru non-participant observation and semi-structured interviews with students and teachers, which were then analyzed using the Miles and Huberman interactive model”. The research results show that parents apply three types of parenting styles, namely “democratic, authoritarian, and permissive”, with the democratic parenting style being the most dominantly applied model. In general, students' learning motivation is at a fairly good level. Democratic parenting has proven to be the most effective in fostering high learning motivation because it successfully creates a balance between aspects of freedom, attention, open communication, and supervision. In contrast, authoritarian parenting tends to trigger extrinsic motivation to avoid punishment, while permissive parenting leads to low responsibility and discipline in students' learning due to minimal control.